A Rare Case of Ischiopagus Dicephalus Conjoined Twins with Tetrabrachius Tripus: Prenatal Diagnosis and Management: A Case Report - Ahsanudin Attamimi; Detty Siti Nurdiati; Irwan Taufiqur Rachman; Adi Ariffianto (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Objectives: This article reports a rare case of conjoined twins with ischiopagus dicephalus and tetrabrachius tripus, emphasizing the significance of early prenatal imaging and interdisciplinary therapy.Case Report: Conjoined twins are a rare congenital anomaly resulting from the incomplete division of a single fertilized ovum in monozygotic, monochorionic, monoamniotic pregnancies. Ischiopagus dicephalus is an exceptionally rare subtype characterized by two heads on a single body, with fusion of the lower thorax and pelvis. We report a 28-year-old primigravida who was diagnosed at 18 weeks’ gestation with ischiopagus dicephalus tetrabrachius tripus. Transabdominal and 3D ultrasonography revealed a unique anatomical combination: two separate heads and two independent hearts and thoracic cavities, yet fused at the lower thorax and pelvis, with a shared liver and gastrointestinal tract and a tri-podal lower-limb configuration. Following multidisciplinary consultation, the "dual-heart yet single-pelvis" anatomy confirmed non-separability and a poor prognosis, leading to the decision for medical termination. A safe second-trimester vaginal delivery was achieved without maternal morbidity.Conclusion: The key learning point is that identifying the specific dual-heart, single-pelvis configuration is a definitive prognostic marker for non-separability. This case emphasizes the critical role of early, accurate prenatal imaging in detecting rare variants of conjoined twins, enabling comprehensive multidisciplinary counseling, informed ethical decision-making, and safe maternal management.Laporan Kasus Langka Kembar Siam Ischiopagus Dicephalus dengan Tetrabrachius Tripus: Diagnosis Prenatal dan Tatalaksana: Laporan KasusAbstrakTujuan: Artikel ini melaporkan kasus langka kembar siam dengan tipe ischiopagus dicephalus dan tetrabrachius tripus, serta menekankan pentingnya pencitraan prenatal dini dan penatalaksanaan multidisiplin.Laporan Kasus: Kembar siam merupakan kelainan kongenital langka yang terjadi akibat pembelahan tidak sempurna dari satu ovum yang telah dibuahi pada kehamilan monozigot, monokorionik, dan monoamniotik. Ischiopagus dicephalus adalah subtipe yang sangat jarang, ditandai dengan dua kepala pada satu tubuh dengan fusi pada toraks bawah dan pelvis. Seorang perempuan primigravida berusia 28 tahun didiagnosis pada usia kehamilan 18 minggu dengan ischiopagus dicephalus tetrabrachius tripus. Ultrasonografi transabdominal dan 3D menunjukkan kombinasi anatomi yang unik: dua kepala terpisah dan dua jantung/rongga dada yang independen, namun menyatu pada toraks bawah dan pelvis dengan fusi hati, saluran pencernaan, serta konfigurasi tiga ekstremitas bawah (tripus). Berdasarkan konsultasi multidisiplin, anatomi "dua jantung namun satu pelvis" mengonfirmasi kondisi janin yang tidak dapat dipisahkan dan prognosis buruk sehingga diputuskan untuk terminasi medis. Persalinan pervaginam trimester kedua yang aman berhasil dilakukan tanpa morbiditas maternal.Kesimpulan: Poin pembelajaran dari kasus ini adalah bahwa identifikasi konfigurasi spesifik dua jantung dan satu pelvis berfungsi sebagai penanda prognostik definitif untuk ketidakmungkinan pemisahan janin. Kasus ini menegaskan peran krusial pencitraan prenatal yang dini dan akurat dalam mendeteksi varian langka kembar siam sehingga memungkinkan konseling multidisiplin yang komprehensif, pengambilan keputusan etik yang tepat, serta penatalaksanaan maternal yang aman.